Redefining leadership: acts of leadership beyond a college classroom - Nichols, Amy E. (Kansas State University, 2016)
This study explored how millennials make sense of leadership in civic life beyond a college classroom. Competency-based learning, specifically as it relates to leadership development, was considered along with the importance of helping others make sense of leadership learning beyond theory to practical application. Competency-based learning considers the practical teaching points set in front of students and posits that they are helpful for making an often nebulous notion of leadership more tangible. The focus of this study was a group of undergraduate millennial-aged college students, selected from a Leadership in Self and Society course. Leadership itself has countless definitions. This study used the definition of leadership according to O’Malley, Fabris McBride and Nichols (2014) as "mobilizing others to do difficult work, work that is more provocative, engaging and purposeful" (p. 50). By examining meanings of adaptive leadership utilizing the described experience of a small subset of students who participated in a college leadership development classroom experience, this study built on a broader notion of how leadership is communicated and understood in a classroom and separately beyond in communities. In considering how operating from the frame of leadership as an activity not a position, data was gathered on how people make sense of acts of leadership and the ambiguity that comes with adaptive situations, by examining the words used to describe their lived experience using a phenomenological research approach. This study strived to build a foundation for other studies to consider articulation of lived leadership experience as a means of building competence within the field of adaptive leadership.
Keywords: Adaptive leadership; Millennial; Leadership behaviors; Sensemaking; Teaching leadership; Competency-based learning